1996
DOI: 10.1200/jco.1996.14.3.821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the treatment of limited-stage small-cell lung cancer.

Abstract: Age is not a significant adverse prognostic variable in SCLC patients with LD. Moderately aggressive chemotherapy may be delivered safely to elderly patients with a good performance status, although modest attenuation of therapy through either dose reduction or omission may occur more frequently in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 0 publications
5
62
1
Order By: Relevance
“…Their median age of 69 years was 9 years younger than in our study (78 years), and there was a higher frequency of septic deaths (8.5%) in their study than in the present study (5.3%). According to the retrospective analysis of Siu et al (1996), 64% of LD patients over 70 years of age who were treated with etoposide and cisplatin alternating with cyclophosphamide+doxorubicin+vincristine developed grade 4 neutropenia. In this study only 19% of patients experienced grade 4 neutropenia (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their median age of 69 years was 9 years younger than in our study (78 years), and there was a higher frequency of septic deaths (8.5%) in their study than in the present study (5.3%). According to the retrospective analysis of Siu et al (1996), 64% of LD patients over 70 years of age who were treated with etoposide and cisplatin alternating with cyclophosphamide+doxorubicin+vincristine developed grade 4 neutropenia. In this study only 19% of patients experienced grade 4 neutropenia (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems better to minimize the risk of unexpected severe toxicity by aspirating massive effusion before the start of chemotherapy. Siu et al (1996) reported the effect of age on the treatment outcome of LD-SCLC. Sixty-nine per cent of patients older than 70 years were capable of receiving full treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies analyzed data related to elderly patients treated with standard chemotherapy regimens and showed substantial toxicity with this therapy, making it inadvisable [42][43][44][45][46][47][48][49][50]. Many authors [42][43][44][45][46][47][48][49][50] found that older patients (≥70 years) treated with optimal chemotherapy had response rates (RRs) and OS rates similar to those in younger patients, although the elderly received less chemotherapy than the planned protocol dose and experienced more toxicity.…”
Section: Same Chemotherapy As Younger Patientsmentioning
confidence: 99%
“…Many authors [42][43][44][45][46][47][48][49][50] found that older patients (≥70 years) treated with optimal chemotherapy had response rates (RRs) and OS rates similar to those in younger patients, although the elderly received less chemotherapy than the planned protocol dose and experienced more toxicity. Table 2 summarizes the main retrospective studies in elderly SCLC patients compared with their younger counterparts and the main retrospective chart reviews.…”
Section: Same Chemotherapy As Younger Patientsmentioning
confidence: 99%
“…In the USA, positive initiatives to address these issues have been taken (Castellucci, 1999). There is substantial evidence to indicate that, with a range of tumour types, given similar treatments, elderly patients have a relative survival similar to that of younger patients (Begg and Carbone, 1983;Dhodapkar et al, 1996;Siu et al, 1996). However, a number of studies have shown that elderly patients often have more advanced tumours at the time of diagnosis (Bergman et al, 1992;Busch et al, 1996;Goodwin et al, 1996) and receive less aggressive treatment (Newcomb and Carbone, 1993;August et al, 1994;Higtower et al, 1994;McKenna, 1994;Newschaffer et al, 1996) than their younger counterparts.…”
Section: mentioning
confidence: 99%